Study of Morphology of Graphene using Atomic Force Microscopy and Raman Spectroscopy - Drewniak, Sabina; Pustelny, Tadeusz; Pasternak, Iwona; Krajewska, Aleksandra; Konieczny, Grzegorz (Photonics Letters of Poland, 2014)
This paper presents the analysis of graphene layer imposed on the resistance sensing structure. All the studies are directed to determine the quantity and quality of the graphene layer. We present the results of the experiments using atomic force microscopy, electron microscopy and Raman spectroscopy. The Raman spectra were subjected to detailed analyzes, especially a position and a half width of 2D peak. Full Text: PDF References T. Pustelny, M. Setkiewicz, S. Drewniak, E. Maciak, A. Stolarczyk, M. Urbańczyk, M. Procek, K. Gut, Z. Oplski, I. Pasternak, W. Strupinski, "The sensibility of resistance sensor structures with graphene to the action of selected gaseous media", Bull. Pol. Ac: Tech. 61, 2 (2013). CrossRef S.-Y. Hong, J.I. Dadap, N. Petrone, P. Ch. Yeh, J. Hone, R.M. Osgood Jr., "Optical Third-Harmonic Generation in Graphene", Phys. Rev. X 3 021014 (2013). CrossRef T. Pustelny, M. Setkiewicz, S. Drewniak, E. Maciak, A. Stolarczyk, M. Procek, M. Urbańczyk, K. Gut, Z. Opilski, I. Pasternak, W. Strupinski, "The Influence of Humidity on the Resistance Structures with Graphene Sensor Layer", Acta Phys. Pol. A 122, 5 (2012). DirectLink L. Liao, Y.-Ch. Lin, M. Bao, R. Cheng, J. Bai, Y. Liu, Y. Qu, K.L. Wang. Y. Huang, X. Duan, "High-speed graphene transistors with a self-aligned nanowire gate", Nature 467(7313), 305 (2010). CrossRef J.-H. Ahn, "Dual-function graphene-based electronic devices", SPIE Newsroom (2014). CrossRef G. Tsoukleri, J. Parthenios, K. Papagelis, R. Jalil, A.C. Ferrari, A.K. Geim, K.S. Novoselov, C. Galiotis, "Subjecting a Graphene Monolayer to Tension and Compression", Small 5, 21 (2009). CrossRef A. Wysmołek, J. Tworzydło, A. Drabińska, Progress in Physics 62, 3 (2011). DirectLink M. Procek, T. Pustelny, A. Stolarczyk, E. Maciak, "Studies of changes in electrical resistance of zinc oxide nanostructures under the influence of variable gaseous environments", Bull. Pol. Ac.: Tech. 62, 4 (2014). CrossRef T. Ciuk, I. Pasternak, A. Krajewska, J. Sobieski, P. Caban, J. Szmidt, W. Strupinski, "Properties of Chemical Vapor Deposition Graphene Transferred by High-Speed Electrochemical Delamination" J. Phys. Chem. C 117, 40 (2013). CrossRef R.K. Joshi, H. Gomez, F. Alvi, A. Kumar, "Graphene Films and Ribbons for Sensing of O2, and 100 ppm of CO and NO2 in Practical Conditions", J. Phys. Chem. C, 114, 14 (2010). CrossRef O. Albrektsen, R.L. Eriksen, S.M. Novikov, D. Schall, M. Karl, S.I. Bozhevolnyi, A.C. Simonsen, "High resolution imaging of few-layer graphene", J. Appl. Phys. 111, 064305 (2012). CrossRef K. Grodecki, "Spektroskopia ramanowska grafenu", Electronic Materials (in Polish), 41, 1 (2013). DirectLink B. Trauzettel, "Od grafitu do grafenu", Progress in Physics (in Polish) 58, 6 (2007). DirectLink J. Yu, M. Shafei, K. Ou, K. Shin, W. Wlodarski, "A Study of Hydrogen Gas Sensing Performance of Pt/Graphene/GaN Devices" (IEEE, 2011). CrossRef H. Kim, A.A Abdala, Ch.W. Macosko, "Graphene/Polymer Nanocomposites", Macromolecules 43, 16 (2010). CrossRef Y.Y. Wang, Z.H. Ni, T.Yu, Z.X. Shen, H.M. Wang, Y.H. Wu, W. Chen, A.T. Shen Wee, "Diffusion of Dextran Probes in a Self-Assembled Fibrous Gel Composed of Two-Dimensional Arborols", J. Phys. Chem. C 112, 29 (2008). CrossRef N. Kim, M.K. Oh, S. Park, S.K. Kim, B.H. Hong, "Effect of Gold Substrates on the Raman Spectra of Graphene", Bull. Korean Chem. Soc. 31, 4 (2010). CrossRef K.N. Kudin, B. Ozbas, H.C. Schniepp, R.K. Prud’homme, I.A. Aksay, R. Car, "Raman Spectra of Graphite Oxide and Functionalized Graphene Sheets", Nano Lett. 8, 1 (2008). CrossRef